2022
DOI: 10.1136/bmjsem-2022-001374
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the adoption and implementation of evidence-based injury prevention training programmes: a narrative review

Abstract: While there is a multitude of evidence supporting the efficacy of injury prevention training programmes, the literature investigating the implementation of these programmes is, in contrast, rather limited. This narrative review sought to describe the commonly reported barriers and facilitators of the implementation of injury prevention training programmes among athletes in organised sport. We also aimed to identify necessary steps to promote the uptake and sustainable use of these programmes in non-elite athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Within the current review, lack of time, whether it be learning, instructing and/or practicing the programme, is a common barrier that plays a significant role in implementation. A recent narrative review focused solely on the barriers and facilitators associated with exercise-based warm-up programmes showed similar conclusions regarding time restrictions 115. Collective themes within this literature for players, coaches and organisations found that reduced buy-in and support at different levels impacted the adoption of NMT warm-up programmes.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Within the current review, lack of time, whether it be learning, instructing and/or practicing the programme, is a common barrier that plays a significant role in implementation. A recent narrative review focused solely on the barriers and facilitators associated with exercise-based warm-up programmes showed similar conclusions regarding time restrictions 115. Collective themes within this literature for players, coaches and organisations found that reduced buy-in and support at different levels impacted the adoption of NMT warm-up programmes.…”
Section: Discussionmentioning
confidence: 87%
“…Facilitators included comprehensive workshops from trained instructors (n=11),53 71 78–80 84 90 96 99 100 112 accessibility of supplementary resources (n=10)82 84 87 89 90 105 114 and uptake/support from multiple stakeholders (n=7) 56 67 84 101 103 105 112. Moreover, suggestions from multiple socioecological levels indicated that increasing programme education and support, increased sport-specific activities and improved awareness of preventive effects, influence NMT implementation success 36 88 89 115 116 Figure 2,. adapted from Basow et al 117 illustrates the contextual factors reported in the literature 117.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The injuries are a limiting factor in performance, and appear frequently in the amateur soccer world (Minnig et al, 2022;Van de Hoef et al, 2017;Ekstrand et al, 2009;van der Horst et al, 2015): moreover, the amateur footballer often cannot have the presence of complete medical and technical staff in every training session.…”
Section: Introductionmentioning
confidence: 99%